Bowel ultrasound in assessment of Crohn's disease and detection of related small bowel strictures: a prospective comparative study versus x ray and intraoperative findings. (1st April 2002) - Parente, F; Maconi, G; Bollani, S; Anderloni, A; Sampietro, G; Cristaldi, M; Franceschelli, N; Bianco, R; Taschieri, A M; Bianchi Porro, G
Abstract : Background and aim: Despite the fact that bowel ultrasound (US) has recently been proved to be useful in the assessment of bowel diseases, uncertainty persists as to its diagnostic role in patients with complicated Crohn's disease (CD). Therefore, we have prospectively investigated the accuracy of US compared with x ray procedures and intraoperative findings in detecting small bowel strictures complicating CD as well as its reliability in assessing disease extent and location within the bowel. Methods: A series of 296 consecutive patients with proven CD admitted to L Sacco University Hospital between 1997 and 1999, having undergone complete radiographic evaluation (including small bowel x ray, colonoscopy, or double contrast barium enema), were enrolled in the study. Bowel US was performed in each patient by two experienced operators unaware of the results of other diagnostic procedures. The accuracy of US in detecting strictures compared with x ray studies was determined separately in two different groups of patients: 211 patients treated conservatively (non-operative CD) and 85 patients who were candidates for surgery for CD complications or unresponsiveness to medical therapy (operative CD). Results: Overall sensitivity and specificity of US in assessing the anatomical distribution of CD were 93% and 97%, respectively. The extent of ileal disease measured at US correlated well with that determined by x ray ( r =0.52, p<0.001) in medically treated patients as well as with that measured intraoperatively in surgical patients ( r =0.64, p<0.001). One or more stenoses were detected in 75 patients (35.5%) at small bowel enteroclysis in the non-operative CD group compared with 70 (82%) in the operative CD series. Sensitivity, specificity, and positive predictive values of bowel US in the detection of strictures were 79%, 98%, and 95% in non-operative CD patients and 90%, 100%, and 100% in operative CD cases, respectively. Conclusions: In experienced hands, bowel US is an accurate technique for assessing CD extent and location and is very helpful in detecting small bowel strictures, especially in very severe cases that are candidates for surgery. The use of bowel US is therefore justified as a primary investigation in CD patients in whom complications are suspected.